Desenvolvimento de novos produtos: pão de forma com polpa de cenoura e de beterraba - Santana, Bruno Fernandes (2007)
Developing new products in dynamic market economies is essential for company survival. The aim of this investigation was to develop sandwich loaf with carrot and beet pulp along the whole productive chain. Analyses were carried out in order to characterize whole and dehydrated carrot and beet pulp utilized in bread making. Values quantified were humidity, ethereal extract, crude fiber, proteins, pH, titratable acidity, ashes, and mineral profile. Results showed significant differences among pulps in all variables. Bread formulations containing pulps were tested apart in a pilot study at 0%, 2,5%, 5,0%, 7,5%, 10,0%, 12,5% rates. Later, carrot and beet whole pulp were tested at 15,0%, 20,0% rates, as well as dehydrated pulps at 0%, 10,0%, 12,5%, 15,0% rates. After baking, the loaves were submitted to sensory analysis by trained and untrained panel, in order to determine the formulation containing both pulps to be used in the same product. Then, formulation was analyzed according to humidity, ethereal extract, protein, pH, titratable acidity, crude fiber, ash, and mineral parameters. Furthermore, bread texture was evaluated as well. Shelf live was assessed up to 17 days focused on Bacillus cereus; total and thermotolerant coliforms; Salmonella sp; fungi; and yeasts. Results showed negative counts for nearly all items. Market analysis included packaging, major competitors, costs, economic viability, and sensory acceptance test. Acceptance rate was over 90%, and product purchase decision showed 100% rate. Finally, costs and economic viability were found to be positive, thereby showing feasibility to product development.